Development of Bacterial Colonies in Dry Fermented Smoked Buffalo Sausages - Berwal, Rajkumar; Chatli, Manish K (Journal of Meat Science, 2012)
Texture and juiciness of fermented sausages directed by the distribution of bacterial colonies in the meat system. A study was conducted to assess the localization of bacterial cultures in fermented smoked and unsmoked dry sausages by employing light microscopy. Scanning electron microscopy was also carried out to determine the morphological processes that take place during manufacture of raw ripened dry sausages from pork and buffalo meat blend. Lactobacillus plantarum (MTCC-1407), Pediocoocus acidilactici (NCIM-2292) and Micrococcus roseus (MTCC-1532) were used as starter cultures in combination of 1:1:1 for fermentation of sausages. On light microscopy, bacterial cultures were seen localized in nests in the fermented sausages. Scanning electron microscopy revealed that closely bound muscle fibres were surrounded by protein net work.
Keywords: Fermented sausages; light microscopy; scanning electron microscopy; starter cultures